Diagnostic heterogeneity in scrub typhus serology: A scoping review of IFA thresholds and regional standardisation needs (2005–2024) - Le, Khanh Kim; Saraswati, Kartika; Wongsantichon, Jantana; Day, Nicholas P. J.; Blacksell, Stuart D. (PLOS Neglected Tropical Diseases, 2025)
Background The indirect immunofluorescence assay (IFA) remains the most widely used reference method for diagnosing scrub typhus. However, inconsistent cut-off thresholds and strain selections across studies hinder standardisation and complicate cross-regional comparisons. This scoping review examines diagnostic heterogeneity in IFA-based scrub typhus serology and assesses the need for region-specific standardisation. Methods We conducted a systematic search of peer-reviewed literature published between January 2005 and May 2024 across PubMed, Scopus, and Web of Science databases. Studies were included if they employed IFA for diagnosing or conducting seroepidemiological investigations of scrub typhus and reported specific IgM or IgG titre thresholds. Data were extracted regarding IFA methodology, antigen strains used, titre cut-offs for positivity, sample populations, and geographic settings. The studies were mapped and synthesised to identify trends, methodological diversity, and regional variation in IFA practices. Results A total of 84 studies met the inclusion criteria, covering 16 countries across Asia-Pacific and South Asia. The diagnostic cut-off titres for IgM ranged widely from 1:10 to 1:25,600, with considerable variability both within and between countries. Many studies lacked a clearly stated rationale for threshold selection or did not reference region-specific validation. Antigen panels were often limited to prototype strains (e.g., Karp, Gilliam, Kato), with few incorporating locally circulating genotypes. Seroprevalence estimates were significantly influenced by the selected cut-off and antigen composition. Only a minority of studies employed standardised or validated thresholds aligned with regional disease endemicity. Conclusion This review underscores significant heterogeneity in IFA cut-offs and strain selection in scrub typhus serology, highlighting the urgent need for regionally validated diagnostic standards. Greater harmonisation of IFA protocols, including rational cut-off determination and inclusion of locally relevant strains, is crucial for improving diagnostic accuracy and informing surveillance and public health strategies.